Disaster Recovery Indicators of Housing Reconstruction: The Story of Post Tsunami Aceh, Indonesia - Azmeri Azmeri; Cut Mutiawati; Nafisah Al-Huda; Hilda Mufiaty (TDMRC, Universitas Syiah Kuala, 2017)
The earthquake and tsunami that hit Aceh in December 2004 have come to represent the worst natural disaster in living memory. Post-disaster housing reconstruction was one of the concerns in re-building a better and safer Aceh. The rehabilitation and housing reconstruction works pose an immense challenge because of lack of expertise, resources, and coordination. This research was aimed to evaluate the housing rehabilitation and reconstruction process after one decade. Focus Group Discussion (FGD) was selected as the main data collection technique to achieve comprehensive discussion among all actors involved in the reconstruction process. It was concluded that there are four indicators that poses as strains and support of post-disaster housing rehabilitation and reconstruction process in Aceh. They are (1) housing delivery process, (2) community participation in housing design and supervision, (3) procurement for building materials and skilled labors, and (4) government involvement and policy. Coordination is also a significant factor that was neglected. Suggestions for better future practices are presented, such as ensuring the accuracy of beneficiaries’ data to avoid overlapping; intensifying the role of government at every stage of the reconstruction processes; engaging the community to be actively involved in rehabilitation and reconstruction process.